Advances in the Pharmacological and Non-pharmacological Management of Non-motor Symptoms in Parkinson's Disease: An Update Since 2017 - VAN WAMELEN, Daniel J.; RUKAVINA, Katarina; PODLEWSKA, Aleksandra M.; CHAUDHURI, K. Ray (Current neuropharmacology, 2023)
Background: Non-motor symptoms (NMS) are an important and ubiquitous determinant of quality of life in Parkinson’s disease (PD). However, robust evidence for their treatment is still a major unmet need. Objective: This study aimed to provide an updated review on advances in pharmacological, nonpharmacological, and exercise-based interventions for NMS in PD, covering the period since the publication of the MDS Task Force Recommendations. Methods: We performed a literature search to identify pharmacological, non-pharmacological, and exercise-based interventions for NMS in PD. As there are recent reviews on the subject, we have only included studies from the 1st of January 2017 to the 1st of December 2021 and limited our search to randomised and non-randomised (including open-label) clinical trials. Results: We discuss new strategies to manage NMS based on data that have become available since 2017, for instance, on the treatment of orthostatic hypotension with droxidopa, several dopaminergic treatment options for insomnia, and a range of non-pharmacological and exercise-based interventions for cognitive and neuropsychiatric symptoms, pain, and insomnia and excessive sleepiness. Conclusion: Recent evidence suggests that targeted non-pharmacological treatments, as well as some other NMS management options, may have a significant beneficial effect on the quality of life and need to be considered in the pathways of treatment of PD.